Common antidepressant side effect profiles and their management: A literature review - Putri, Nazwa Kania; Nasution, Artika Ananda Putri; Ratna, Maya Ganda; Putri, Giska Tri (JOURNAL OF Mental Health Concerns, 2026)
Background: Antidepressant medications are widely used as a first-line treatment for depressive disorders and various other mental health conditions in both primary and hospital-based healthcare settings. Despite their proven efficacy in alleviating depressive symptoms, antidepressants are frequently associated with a range of adverse effects that may negatively impact patient adherence, treatment satisfaction, and long-term therapeutic outcomes. Understanding the safety profile of antidepressants is therefore essential for optimizing clinical management and improving treatment success. Purpose: To review and synthesize current scientific evidence regarding the commonly encountered adverse effect profiles of antidepressant medications and the strategies used for their management in clinical practice. Results: A literature review of studies published between 2020 and 2025 identified several frequently reported adverse effects associated with antidepressant use, including gastrointestinal disturbances, sleep disorders, sexual dysfunction, weight changes, and neurological symptoms such as headache and tremor. The adverse effect profiles varied across antidepressant classes, including selective serotonin reuptake inhibitors (SSRIs), serotonin–norepinephrine reuptake inhibitors (SNRIs), tricyclic antidepressants, and atypical antidepressants. Management strategies commonly reported in the literature included dose adjustment, switching antidepressant agents or drug classes, the use of adjunctive therapies to alleviate specific adverse effects, and continuous patient education and monitoring to enhance treatment tolerability and adherence. Conclusion: Antidepressant medications exhibit diverse adverse effect profiles that may compromise treatment effectiveness if not appropriately addressed. This literature review highlights the importance of recognizing commonly encountered adverse effects and implementing individualized, evidence-based management strategies to improve drug tolerability and patient adherence. An integrated and patient-centered approach is essential to optimize antidepressant therapy in clinical practice. Keywords: Antidepressants; Adverse Effects; Drug Safety Profile; Management; Literature Review.